Moses C. Pilsbury family papers - Pilsbury, Moses C. (Moses Cross), 1778-1848.; Pilsbury, Amos, 1805-1873.; Walker, Galen C., -1856.; Walker, Lois Cleveland
Chiefly correspondence relating to family affairs and to concerns of Amos Pilsbury as warden (1830-1845) of the Connecticut State Prison, Wethersfield, Conn., and as superintendent (1845-1855) of the Albany Penitentiary, Albany County, N.Y., and of Galen C. Walker as deputy warden (1850-1856) of the Massachusetts State Prison, Boston, Mass. Also includes a contract (9 Aug. 1833) for the hire of convict labor signed by Amos Pilsbury while warden of the Connecticut State Prison, condolences following the 1856 murder of Walker by a prison inmate, a letter (27 Mar. 1864) to Lois Cleveland Walker from a son during his Civil War service, and genealogical material pertaining to the Pilsbury family.
Pilsbury (Pillsbury) family members represented include Moses C. Pilsbury, his son Amos, Moses's daughter Lois Cleveland (Pilsbury) Walker, and her husband Galen C. Walker.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Pillsbury family; Pillsbury family -- Correspondence; Albany Penitentiary (Albany County, N.Y.); Connecticut State Prison (Wethersfield, Conn.); Massachusetts State Prison; Convict labor; Prison homicide -- Massachusetts; Prisons -- Connecticut -- Wethersfield; Prisons -- Massachusetts -- Boston; Prisons -- New York (State) -- Albany County; United States -- History -- Civil War, 1861-1865.; Prison wardens